Temperature dependent electrical characteristics of Pt Schottky barriers fabricated on lightly and highly doped n-type 4H-SiC. (2nd October 2015) - Huang, Lingqin; Wang, Dejun
Abstract: The temperature dependent electronic characteristics of Pt Schottky barriers fabricated on lightly and relatively highly doped n-type 4H-SiC (1 × 10 16 and 1 × 10 18 cm −3 ) are comparatively investigated. It is found that the abnormal temperature dependence of barrier height and ideality factor estimated from the thermionic emission (TE) model for both lightly and highly doped samples could be successfully explained in terms of Gaussian distribution of inhomogeneous barrier heights. However, the estimated mean barrier height according to Gaussian distribution for the highly doped sample is much lower than the actual mean value from the capacitance–voltage ( C – V ) measurements. Interestingly, the values of barrier height from the thermionic field emission (TFE) model are found to be close to those from the C – V measurements, indicating that the TFE model is more appropriate to explain the electrical transport for the highly doped sample.